Perilaku Cyberbullying Mahasiswa dengan Teman Sebaya - Siti Khanifah Putri Kurnia Pratiwi; Rina Sari Kusuma (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2019)
The development of communication and information technology changes the community’s online communication pattern gradually, to elicit the toxic behavior disinhibition online effect where lack of self-control or even tends to be aggressive when Communicate online rather than communicating directly. These aggressive behaviors are then demonstrated in cyberbullying action. Cyberbullying is an aggressive, intense, and repetitive behaviour that is performed using forms of technology and electronics as a medium to attack a person. This research purposes are to acknowledge the self concept of cyberbullying suspect and their forms of cyberbullying. This research is a qualitative research aiming to understand the phenomenon of cyberbullying among UMS students. The trait of this research is descriptive as its suppose to serve comprehensive objective description over the tangible situation of the observed object. The researcher uses the snowball sampling in order to define the observation subject which considered may provide proper information for this research and obtained by three people. The data collecting technique is depth interviews. In this research it shows the action of cyberbullying suspect is possessed by student with both positive and negative self concept. Some forms of cyberbullying are flamming, harassment, denigration, cyber-stalking, impersonation, outing, and exclusion. These actions of cyberbullying done by use of social media, both messenger and public social media.